Adsorption properties of β-carotene on mesoporous carbon-coated honeycomb monolith: kinetics, thermodynamics, and regeneration studies - How, Cai-Kian; Soltani, Soroush; Chuah, Teong-Guan; Phuah, Eng-Tong; Choong, Thomas Shean-Yaw (Springer, 2022)
A facile synthesis procedure of mesoporous carbons coated monolith (MCCM) adsorbent was accomplished using furfuryl alcohol as carbon precursor, triblock copolymer Pluronic F-127 as the structure-directing agent, pyrrole as the binder for polymerization with nitric acid as catalyst and inorganic cordierite as substrate through dip-coating method. Surface chemistry revealed the dominance of acidic sites over adsorbents surface with the majority of active sites occupied by the phenolic and carboxylic groups. The MCCM adsorbent exhibited representative Type IV isotherm with a uniform-distributed PSD plot centered at 6.18 nm. A thermodynamics study involving Langmuir and Freundlich models was applied to establish the adsorption equilibrium data at temperatures of 30 to 50 °C. The Freundlich model best described the experiment data with maximum adsorption capacity of β-carotene onto MCCM was 192.64 mg/g. Three kinetic models, Lagergren first-order, pseudo-second-order and intra-particle diffusion models, were employed to investigate the adsorption mechanism of β-carotene molecules onto active surface sites of MCCM adsorbent. Both the Lagergren first-order and pseudo-second-order kinetic models fitted with experimental data with the latter described perfectly with higher regression coefficient value (R2>0.99). Intra-particle diffusion featured the involvement in β-carotene adsorption mechanism, but it was not the sole rate-limiting step. The negative value of Gibbs free energy change (ΔGo) suggested the spontaneity of β-carotene adsorption process. In contrast, the positive values of enthalpy change (ΔHo) and entropy change (ΔSo) demonstrated the endothermic nature and entropy-driven of the adsorption process, respectively. The increased ΔGo with T indicated an increased degree of spontaneity at high temperatures. Regeneration studies of MCCM adsorbent exemplified a slight decrease in adsorption capacities after three consecutive regeneration cycles.